Cardiac fibroblasts acquire properties of matrifibrocytes in vitro and in mice with pressure overload-induced congestive heart failure. (25th November 2020) - Herum, K.M; Gilles, G; Romaine, A; Melleby, A.O; Christensen, G; McCulloch, A.D; Brakebusch, C.H
Abstract: Introduction: Activation of cardiac fibroblasts (CFB) is a key step in development of fibrosis in the heart. It was recently shown that, in addition to the well-studied myofibroblast (myoFB) phenotype, activated cardiac fibroblasts can adopt a newly defined matrifibrocyte phenotype, characterized by expression of extracellular matrix (ECM) genes associated with bone, cartilage and tendon development. However, it is unknown whether matrifibrocytes exists in the pressure-overloaded fibrotic and failing heart, and whether substrate stiffness drives differentiation. Hypothesis: Matrifibrocyte differentiation occurs in vitro during culturing of primary cardiac fibroblasts, and in vivo in response to left ventricular pressure overload. Methods: Left ventricular pressure overload induced by o-ring aortic banding (ORAB) induced cardiac phenotypes of concentric hypertrophic remodelling and congestive heart failure. Primary CFB from adult mice were cultured on plastic or soft polyacrylamide hydrogels (4.5 kPa) for various times. mRNA expression of phenotypic markers were measured by RT-PCR. Presence of smooth muscle α-actin (SMA) fibers was determined by immunocytochemistry. Results: ECM genes normally expressed in bone and cartilage (COMP, CILP-2, OPG and SCX) were upregulated in hypertrophic left ventricles of mice with congestive heart failure. The myoFB marker acta2 was increased 2 weeks after ORAB, returned to baseline at 4 weeks and increased again at 20 weeks when the left ventricle was dilating and failing, indicating that the myoFB phenotype is not permanent. In vitro, primary CFB upregulated bone/cartilage-associated ECM genes after 12 days of culturing on plastic. Acta2 mRNA and SMA protein levels peaked after 9 days in culture whereafter they declined, indicating a shift in phenotype. Culturing primary CFB on soft (4.5 kPa) hydrogels delayed, but did not prevent, myoFB differentiation while expression of bone/cartilage ECM genes was absent or low, indicating that high stiffness is a driver of the matrifibrocyte phenotype. Blockers of mechanotransduction, SB431542 (TGFβRI inhibitor), Y27623 (ROCK inhibitor) and cyclosporine A (calcineurin inhibitor), completely inhibited myoFB differentiation but upregulated several matrifibrocyte markers, indicating that distinct signaling pathways regulate myoFB and matrifibrocyte differentiation. Removing inhibitors re-induced myofibroblast markers in cells on plastic but not on soft gels consistent with high stiffness promoting myofibroblast differentiation. Conclusion: Primary cardiac fibroblasts acquire characteristics of matrifibrocytes in vitro when cultured for long time on plastic and in vivo in left ventricles of mice with pressure overload-induced congestive heart failure. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): Marie Sklodowska-Curie Individual Fellowship